Comparison of gabapentin with estrogen for treatment of hot flashes in post-menopausal women - Zahra Allameh; Safoura Rouholamin; Sonia Valaie (Wolters Kluwer Medknow Publications, 2013)
Objective: Various non-hormonal agents have been used for the treatment of hot flashes in women with menopause. Some studies have reported that gabapentin appears to be an effective and well-tolerated treatment modality. The aim of this study was to evaluate whether the treatment with gabapentin is effective in reducing hot flash frequency and severity and also to compare gabapentin 100 mg/day, 300 mg/day and conjugated estrogen in this regards. Methods: In this comparative clinical trial, 100 post-menopausal women attending outpatient clinics of Isfahan University hospitals were included from April 2008 to February 2009. Participants randomly received gabapentin 300 mg/day, gabapentin 100 mg/day, or conjugated estrogen 0.625 mg/day for 12 weeks. Frequency and severity of hot flashes and adverse effects were compared among the three groups. Findings: From all, 16 participants dropped out. There were no significant differences among the groups before intervention in terms of age, body mass index and baseline hot flash frequency and severity. Hot flash diaries were used to record the frequency and severity of hot flashes. After the treatment period, there was a significant decrease in both severity and frequency of hot flashes in all three groups. Post-hoc analyses showed that the frequency and severity of hot flashes were significantly lower in those who received gabapentin 300 mg/day or estrogen 0.625 mg/day compared to those who received gabapentin 100 mg/day. There was not statistically significant difference between those who received gabapentin 300 mg/day and those who received estrogen. Very few adverse effects, mostly gastrointestinal discomfort were observed in both gabapentin groups (8%). Conclusion: Gabapentin 300 mg/day could be useful to relieve hot flashes in women for whom hormone therapy is not suitable or when hot flashes do not respond to other therapies. Further researches are needed to determine the efficacy of gabapentin use for longer periods or at higher doses.